The Hospitallers and the Holy Land financing the Latin East, 1187-1274 - Bronstein, Judith 1964- (Suffolk Boydell & Brewer, 2005)
The Order of the Hospital of St John was among the most creative and important institutions of the Middle Ages, its history provoking much debate and controversy. However, there has been very little study of the way in which it operated as an organisation contributing to the survival of the Christian settlement in the East, a gap which this book addresses. It focuses on the impact of the various crises in the East upon the Order, looking at how it reacted to events, the contributions that western priories played in the rehabilitation of the East, and the various efforts made to restore its economic and military strength. In particular, the author shows the key role played by the papacy, both in the Order's recovery, and in determining the fate of the crusader states. Overall, it offers a whole new perspective on the connections between East and West. JUDITH BRONSTEIN gained her Ph.D. from the University of Cambridge.
The Hospitallers in the Holy Land, 1187-1274 -- The order in the West and crises in the Latin East -- The Popes, the Hospitallers, and crises in the Holy Land -- Members of the order serving in the Latin East and in the French priories
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: Church history, 12th century; Church history, 13th century; Church History -- 12th century; Church History -- 13th century; Hospitalers; Church history ; 12th century; Church history ; 13th century